2019
DOI: 10.1101/865204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Distinct Contractile Injection System Found in a Majority of Adult Human Microbiomes

Abstract: 30

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…However, we detected a mild eCIS enrichment in the human gut commensal Bacteroides ( Figure 1B) and Parabacteroidetes genera. Bacteroides was recently reported by the Shikuma group as being eCIS-rich 28 .…”
Section: Ecis Presence Is Highly Correlated With Specific Ecosystemsmentioning
confidence: 96%
“…However, we detected a mild eCIS enrichment in the human gut commensal Bacteroides ( Figure 1B) and Parabacteroidetes genera. Bacteroides was recently reported by the Shikuma group as being eCIS-rich 28 .…”
Section: Ecis Presence Is Highly Correlated With Specific Ecosystemsmentioning
confidence: 96%
“…MACs are one example of contractile injection systems (CISs), which are related to the contractile tails of some bacteriophage [the viruses of bacteria (Figure 4c Since the discovery of MACs, related CISs have been discovered that also form multi-CIS complexes (13). In addition to stimulating metamorphosis, closely related structures were found to mediate interactions between microbes and amoebae, insects, and potentially humans (13,132,159,172). While a number of pathogenic bacteria use type VI secretion systems to inject protein toxins into target cells to cause disease (97), MACs are the first CIS to promote a beneficial microbeanimal interaction.…”
Section: A Surprisingly Different Way That Bacteria Stimulate Metamor...mentioning
confidence: 99%
“…Finally, bacteria-stimulated metamorphosis is a widespread example of a beneficial host-microbe interaction, yet it is a largely unexplored space for mining of biomedical and biotechnology applications. For example, based on our discovery of MACs, we identified a new and previously undescribed family of CISs that are produced by Bacteroidales bacteria commonly found in the human gut (132). Such systems inject contents into diverse animal cell types and could someday be modified as nanometer-scale devices for the delivery of specific proteins into target cells (130).…”
Section: Applied Potential Of Studying How Bacteria Stimulate Animal ...mentioning
confidence: 99%
“…The products bacteria produce to promote Hydroides metamorphosis and the machinery Hydroides uses to sense these products could lead to broader discoveries about mechanisms and tools for host-microbe interactions. For example, we found that gene clusters encoding Contractile Injection Systems originally discovered to promote Hydroides metamorphosis are strikingly similar to gene clusters found in Bacteroidales bacteria from healthy human microbiomes 62 . Moreover, understanding the payload delivery and targeting mechanism of the MACs produced by P. luteoviolacea could enable us to produce new types of therapeutic delivery systems 63 .…”
Section: Biotechnology and Bacterial Productsmentioning
confidence: 61%